Calcareous sponges of Indonesia - Soest, Rob W.m. Van (Zootaxa, 2015)
The calcareous sponges collected during Indonesian-Dutch research projects, incorporated in the collections of the Naturalis Biodiversity Center (formerly the Rijksmuseum van Natuurlijke Historie and the Zoölogisch Museum of the University of Amsterdam), are described and discussed. A total of 37 species were distinguished, of which 16 are new to science, while several others are very poorly known. The new species are Clathrina purpurea sp.nov., Clathrina beckingae sp.nov., Clathrina sororcula sp.nov., Arthuria tubuloreticulosa sp.nov., Ernstia indonesiae sp.nov., Ernstia chrysops sp.nov., Ernstia klautauae sp.nov., Ernstia naturalis sp.nov., Ascandra kakaban sp.nov., Ascandra crewsi sp.nov., Ascaltis angusta sp.nov., Pericharax orientalis sp.nov., Sycetta vinitincta sp.nov., Anamixilla singaporensis sp.nov., Grantessa borojevici sp.nov. and Grantessa tenhoveni sp.nov. An additional six species reported from Indonesia, but not represented in our material, are briefly characterized.